If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3y + -2) = 7(y + -2) Reorder the terms: 3(-2 + 3y) = 7(y + -2) (-2 * 3 + 3y * 3) = 7(y + -2) (-6 + 9y) = 7(y + -2) Reorder the terms: -6 + 9y = 7(-2 + y) -6 + 9y = (-2 * 7 + y * 7) -6 + 9y = (-14 + 7y) Solving -6 + 9y = -14 + 7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7y' to each side of the equation. -6 + 9y + -7y = -14 + 7y + -7y Combine like terms: 9y + -7y = 2y -6 + 2y = -14 + 7y + -7y Combine like terms: 7y + -7y = 0 -6 + 2y = -14 + 0 -6 + 2y = -14 Add '6' to each side of the equation. -6 + 6 + 2y = -14 + 6 Combine like terms: -6 + 6 = 0 0 + 2y = -14 + 6 2y = -14 + 6 Combine like terms: -14 + 6 = -8 2y = -8 Divide each side by '2'. y = -4 Simplifying y = -4
| h(-2)=15t-3t*2 | | 0.69(10n+25)=10+5n | | -8x-12=7x-22 | | 4(10t-7)=3(6t-2) | | 20.4=4c | | 5(2p+2)=6(p+5) | | 30-5x(3+1)= | | 0.3n+1.1=0.8(6+5n) | | 8squared= | | 4x+8=6x-3 | | y-5=10(x-1) | | 4n=5 | | P-8+4p= | | 9+12=711 | | 25=q+14 | | 5(4a+7)=3(8a+a) | | 7+6n+4-3n= | | 5(x+2)-3(x-4)=7-x | | 8-7p=12-5p | | Y=sec(x^3) | | 8y+43-7y=75 | | 4c-5(x+1)+11=0 | | Y=3tan*4x | | x+(x*.0875)=20.12 | | 5(2x-7)=0 | | 2y+x=8.5 | | 2x^3+10x^2-2x-10=0 | | 6x+29=65 | | 4x=-2x-42 | | 3x+2.5=4x-35 | | 4(2-2y)+6=2(7+4y) | | 18x-3y=6 |